Application Of Guided Inquiry Model To Improve The Ability And Critical Thinking Disposition Of Senior High School Students In Physics Learning - Maolani, Agni Gina; Warliani, Resti; Irvani, Asep Irvan (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study aims to examine the effectiveness of the Guided Inquiry model in improving students' critical thinking ability and disposition on alternative energy materials. The research design used a pseudo-experiment with a quantitative approach. The research subjects consisted of 70 X grade students who were divided into two groups, namely the experimental group (Guided Inquiry) and the control group (Problem-Based Learning). The results showed that the increase in CTA and CTD of the experimental class was significantly greater than the control. Critical thinking ability increased from 37.26 to 74.03, and critical thinking disposition from 54.00 to 67.89. T-test and effect size analysis showed significant differences and a large impact. There was a positive correlation between critical thinking skills and disposition (r = 0.483; p < 0.001). The Guided Inquiry model proved effective in developing students' overall critical thinking skills.